An exploration of Mary Wollstonecraft’s writings: Mary, a fiction and letters written during a short residence in Sweden, Norway and Denmark - Guho, Shejuty (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2017.